2007
DOI: 10.1001/archpedi.161.12.1183
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Corpus Callosum in Adolescents Born Preterm

Abstract: The corpus callosum grows dramatically in VPT adolescents, and this growth is associated with neuropsychological outcome. This may represent a delay of a normal maturational process in VPT individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
4
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 38 publications
6
59
4
2
Order By: Relevance
“…Moreover, data in the literature reported that preterm born people have a smaller corpus callosum (37). Information about preterm birth was not available in our population.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, data in the literature reported that preterm born people have a smaller corpus callosum (37). Information about preterm birth was not available in our population.…”
Section: Discussionmentioning
confidence: 93%
“…39 Greater callosal maturation is also associated with greater motor function. 54 Moreover, correlations between Verbal and Non-verbal IQ 55,56 and the posterior corpus callosum have previously been reported in adolescents born preterm. 9,56 In the subgroup analysis of field strength, the difference in fractional anisotropy in the genu of the corpus callosum was significantly greater in the 3T group than in the 1.5T group, and heterogeneity was found in the 3T group in this subregion.…”
Section: Review 335mentioning
confidence: 87%
“…Thus, there seems to be some support for the finding of a smaller posterior CC in those born with LBW and VLBW. Whether this smaller posterior CC represents a permanent change or merely delayed growth is still unclear, because the CC is believed to reach maturity in young adulthood, 33 ie, slightly older than those included in our cohort. A previous study 33 reported evidence for a growth spurt of CC between 14 -15 years and 23 years in a group of 72 prematurely born subjects.…”
Section: Discussionmentioning
confidence: 98%
“…The splenium forms after the genu and the callosal body, and even though the mature shape of the CC is reached by 17 weeks of gestation, premature birth may interfere with its later stages of development. 33 In addition, the reduced size of the posterior CC may reflect important changes within the microstructure. In a quantitative study of VLBW adolescents, including DTI, 35 a lower fractional anisotropy was detected in posterior aspects of CC.…”
Section: Discussionmentioning
confidence: 99%